Modeling the behavioural intention of broadband technology usage among teenagers: application of UTAUT Model - Muraina, Ishola D.; Sheik Osman, Wan Rozaini; Ahmad, Azizah; Ibrahim, Huda; Mohd Yusof, Shafiz Affendi (Medwell Journals, 2016)
Teenagers in any society are fond of using the internet services on the mobile devices in lieu of personal computer, thus affect their behavioural intention in using broadband technology.Studies on the factors that affect the behavioural intention of teenagers towards the usage of broadband technology have been received less attention.This research proposes the model for behavioural intention of broadband technology usage among the teenagers by adapting unified theory of acceptance and use of technology model.A quantitative survey approach was employed by engaging 1,730 teenagers who are secondary school students in the Northern region of Malaysia.The result reveals that performance expectancy, effort expectancy, social influence and compatibility are the significant factors to achieve behavioural intention of usage of broadband technology among the teenagers. The use of presented model would help in determining the behaviour of teenagers towards the use of broadband technology which can affect their academic performance.